Perancangan Sistem Informasi Geografis Berbasis Web Untuk Pendataan Penderita Gizi Buruk: (Studi Kasus : Kecamatan Kota Waingapu) - Hendy Umbu Daungu Niga; Pingky Alfa Ray Leo Lede; Hawu Yogia Pradana Uly (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The representation process for mapping malnutrition rates in the Waingapu City District area does not yet use computer technology, so the process of monitoring malnutrition rates in each region is still not presented well. This certainly makes it difficult for cadres and the Health Service to monitor the rate of malnutrition in the Waingapu City District Area. Therefore, it is necessary to build an information system that is able to provide data, both in the form of graphs and maps, for mapping malnutrition rates in the Waingapu City District area. The design and development of this information system was carried out using data collection methods and direct interviews with the Waingapu City Health Service, by looking for other references related to similar research. The aim of designing a web-based geographic information system for data collection on malnutrition sufferers is to help the community and the Health Service in monitoring and handling cases of malnutrition in the Waingapu City District area. This Geographic Information System will display malnutrition data based on sub-districts using color polygons as signs that provide information about safe conditions or conditions that require further treatment. The method used in creating a website is waterfall and goes through six stages, namely: the Reguirement Analysis (Analysis), Design (design), Development (coding), Testing (trial), and maintenance (maintenance) stages and system testing is carried out using black box.